2018
DOI: 10.3389/fevo.2018.00078
|View full text |Cite
|
Sign up to set email alerts
|

Relative Importance of Habitat Characteristics and Interspecific Relations in Determining Terrestrial Carnivore Occurrence

Abstract: Carnivores act as top-down regulators in terrestrial ecosystems, and their occurrence and relative abundance is a result of complex interactions between food and habitat availability, human pressure (e.g., trapping, hunting, roadkill), and intraguild interactions (competition, predation). Eastern United States has a long history of human impact, which resulted in an altered carnivore community. Specifically, Ohio presents an interesting case for evaluating the relative roles of interspecific relations and habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…In a rare experimental study, Henke & Bryant (1999) found that RAB of Grey Foxes in western Texas increased following removal of Coyotes. However, negative effects of Coyotes were often weak or not statistically significant (Borchert 2012;Lombardi et al 2017;LeFlore et al 2019) and two studies reported positive effects (Rota et al 2016;Rich et al 2018). Showing similar contrasts, LeFlore et al ( 2019) reported near complete temporal overlap between Coyotes and Grey Foxes (Figure 5) while Lesmeister et al (2015) found that these foxes were detected less frequently during nights when Coyotes were also detected.…”
Section: Co-occurrence With Dominant Carnivoresmentioning
confidence: 89%
See 2 more Smart Citations
“…In a rare experimental study, Henke & Bryant (1999) found that RAB of Grey Foxes in western Texas increased following removal of Coyotes. However, negative effects of Coyotes were often weak or not statistically significant (Borchert 2012;Lombardi et al 2017;LeFlore et al 2019) and two studies reported positive effects (Rota et al 2016;Rich et al 2018). Showing similar contrasts, LeFlore et al ( 2019) reported near complete temporal overlap between Coyotes and Grey Foxes (Figure 5) while Lesmeister et al (2015) found that these foxes were detected less frequently during nights when Coyotes were also detected.…”
Section: Co-occurrence With Dominant Carnivoresmentioning
confidence: 89%
“…Other studies evaluating temporal variation in RAB or occupancy of this species were conducted over relatively short (<3 year) periods (Chamberlain et al 1999;Cunningham et al 2006;Gallina et al 2016). In contrast, Bauder et al (2020) found evidence of declines in Grey Foxes in Illinois over 43 years and two studies in the midwestern USA found that they were the least prevalent species in the native carnivore community (Lesmeister et al 2015;Rich et al 2018). Lesmeister et al (2015) found that site extinction rates for these foxes were higher than site colonization rates, and other studies have suggested declines of Grey Foxes in the midwestern USA (Cooper et al 2012).…”
Section: J Ttmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected variables that were known or suspected to influence species distribution based on previous studies on the species from the region (e.g. lynx—Maletzke et al., 2008; bobcats—Clare et al., 2015; cougars—Koehler & Hornocker, 1991; black bear—Long et al., 2007; wolves—Fuller et al., 2003; coyote—Rich et al., 2018; badgers—Apps et al., 2002). Variables representing similar processes were grouped into distinct models for testing to reduce the total number of models tested.…”
Section: Methodsmentioning
confidence: 99%
“…The coexistence of large carnivores in an ecosystem according to the spatial-temporal overlap and niche overlap of different species of prey depends on the reaction towards each other (Pereira et al 2012). The complex environment also defines the ecology of population both wild carnivores and wild preys (Qi et al 2020), and the dynamics of habitat (Rich et al 2018). Understanding the spatio-temporal occurrence of large carnivores along with their preys could be used for conserving the species and populations (Davis et al 2018) in this changing world's environment (Frey et al 2017).…”
Section: Introductionmentioning
confidence: 99%